Post-exercise ingestion of a unique, high molecular weight glucose polymer solution improves performance during a subsequent bout of cycling exercise - Stephens, F. B.; Roig, M.; Armstrong, G.; Greenhaff, P. L. (Journal of Sports Sciences, 2008)
The aim of the present study was to determine the effect of post-exercise ingestion of a unique, high molecular weight glucose polymer solution, known to augment gastric emptying and post-exercise muscle glycogen re-synthesis, on performance during a subsequent bout of intense exercise. On three randomized visits, eight healthy men cycled to exhaustion at 73.0% (s = 1.3) maximal oxygen uptake (90 min, s = 15). Immediately after this, participants consumed a one-litre solution containing sugar-free flavoured water (control), 100 g of a low molecular weight glucose polymer or 100 g of a very high molecular weight glucose polymer, and rested on a bed for 2 h. After recovery, a 15-min time-trial was performed on a cycle ergometer, during which work output was determined. Post-exercise ingestion of the very high molecular weight glucose polymer solution resulted in faster and greater increases in blood glucose (P < 0.001) and serum insulin (P < 0.01) concentrations than the low molecular weight glucose polymer solution, and greater work output during the 15-min time-trial (164.1 kJ, s = 21.1) than both the sugar-free flavoured water (137.5 kJ, s = 24.2; P < 0.05) and the low molecular weight glucose polymer (149.4 kJ, s = 21.8; P < 0.05) solutions. These findings could be of practical importance for athletes wishing to optimize performance by facilitating rapid re-synthesis of the muscle glycogen store during recovery following prolonged sub-maximal exercise.